OPTIMIZING THE TREATMENT OF PATIENTS WITH ACUTE SENSORINEURAL PAIN - Takhsinovna, Nasretdinova Makhzuna; Alisherovich , Normuradov Nadirjon; Nazarovna, Normirova Nargiza (PT. Antis International Publisher, 2025)
Objective: This study aims to evaluate the outcomes of treating patients with acute neurosensory hearing loss across different age groups. The research emphasizes the restoration of hearing as a complex, multi-level process, focusing on the highest level responsible for ensuring proper sensory-motor correction of functional activities. Methods: Hearing restoration was examined using advanced methods, including posturography, which provided insights into sensory-motor adjustments. The study involved patients from varied age demographics, ensuring a comprehensive analysis of age-related differences in treatment responses. Results: The findings demonstrate significant improvements in hearing restoration across all age groups. Posturography proved instrumental in facilitating sensory-motor corrections, highlighting its efficacy as part of a structured rehabilitation process. Age-specific variations in recovery patterns were also observed, providing valuable data for tailoring treatment protocols. Novelty: This research introduces a novel approach by integrating posturography into the treatment framework for acute neurosensory hearing loss. The study underscores the importance of addressing sensory-motor functions as a critical element of hearing restoration, particularly in a multi-level rehabilitation context.